Teachers’ Knowledge and Perception of Practice of School Health Services in Demsa Local Government Area, Adamawa State, Nigeria - Anetor, Gloria O. (International Journal of Human Kinetics, Health and Education, 2023)
This study was conducted to assess teachers‟ knowledge and practice of school health services (SHS) in government secondary schools in Demsa local government area of Adamawa state. A descriptive survey design was used and a multistage sampling technique was employed to select 100 participants for the study, although 94 participants returned the questionnaire. A self-developed validated questionnaire was the instrument for data collection. Data was analyzed using frequency counts, percentages and mean; Chi-square and Pearson Correlation (at 0.05 and 0.01 significant level respectively) were used to analyze the two hypotheses and one research question in the study. Major findings: Teachers had adequate knowledge of SHS (p = 0.000< 0.05); the practice of SHS was not good enough (average practice mean was 2.70): sanitary sites in the schools were not adequate, the lighting and safety within the school environment was inadequate and the teachers appear not to practice adequate general hygiene inspection of the students. Also, the two wards used had positive moderate correlation of SHS (r = 0.248; p .000<0.01). It was concluded that SHS are unsatisfactory in Demsa Local Government area of Adamawa State. Therefore, there is need for all stakeholders involved in implementing SHS in Adamawa state in general and Demsa LGA in particular (Teachers, health workers, parents, government) to collaborate in providing the materials and manpower needed to achieve effective SHS in the area.